The new methodologies for learning how to teach a foreing language by using virtual tools - Flamenco Hernández, Melissa Valeria; Orellana Castro, Marvin Alfredo; Portal Vides, Rocío de Lourdes (2024)
The present report is aimed to present the results of the activities conducted and the knowledge acquired during the practice and development of the specialization course. Throughout virtual learning theories and the theories of learning, the learning process in a virtual modality is presented and detailed, as well as the LMS (Learning Management System) and the online tools that can be used as resources for online classes. Moreover, some of the conducted activities via virtual tools such as Powtoon, Genially, Flippity, and Flipgrid are presented. These activities helped the group not only to learn how to use them and get a better idea of the advantages, but also to get prepared to teach in a virtual environment. Finally, recommendations and conclusions are presented to state the importance and the relevance of the development of the specialization course. Keywords: Virtual Platforms ; Virtual Tools ; Virtual Environments ; Virtual Contents ; Electronic Learning ; Learning Theories.